Babymouse. [5], Heartbreaker - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2006)
Valentine's Day is Babymouse's favorite holiday, but this year there's going to be a dance and Babymouse is desperate to find a date for it.
Horn Book Starred
3.3
3-6.
3-6
Keywords: Animals -- Fiction; Cartoons and comics; Mice -- Fiction; Valentine's Day -- Fiction; Animals -- Fiction; Comic books, strips, etc; Mice -- Fiction; Valentine's Day -- Fiction; Graphic novels